2003
DOI: 10.1016/s0021-9614(03)00094-6
|View full text |Cite
|
Sign up to set email alerts
|

Materials in thermodynamic potential gradients

Abstract: In materials that are exposed to thermodynamic potential gradients (i.e., gradients of chemical potentials, electrical potential, temperature, or pressure), transport processes of the mobile components occur. These transport processes and the coupling between different processes are not only of fundamental interest, but are also the origin of degradation processes, such as kinetic demixing and decomposition and changes in the morphology of the material, all of which are of great practical relevance. Two classe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 32 publications
1
55
0
Order By: Relevance
“…Abbreviations: ppolycrystalline; sc-single crystal; c-cubic; b-bulk; gb-grain boundaries. (1) Ho in p BaTiO3 gb [11]; (2) Ho in p BaTiO3 b [11]; (3) Ni in p Ba(Ho,Ti)O3 [10]; (4) Ni in sc BaTiO3 [10]; (5) Ni in p BaTiO3 [10]; (6) Si in MgSiO3 [39]; (7) 49 Ti in sc (La,Sr)TiO3 [25]; (8) Zr in sc BaTiO3 [12]; (9) 141 Pr in LaFeO3 gb [40; (10) 141 Pr in LaCoO3 gb [40]; (11) Co in LaCoO3 gb [41]; (12) Cr in LaMnO3 [42];(13) Mn in LaCoO3 [43]; (14) Co in LaCoO3 b [41]; (15) 141 Pr in LaMnO3 [40]; (16) Co in GdCoO3 [44]; (17) Co in EuCoO3 [44]; (18) Co in SmCoO3 [44]; (19) Co in NdCoO3 [44]; (20) Co in PrCoO3 [44]; (21) 50 Cr in (La,Ca)CrO3 gb [45]; (22) Co in LaCoO3 [44]; (23) Mn in LaMnO3 b [42]; (24) Mn in LaMnO3 gb [42]; (25) Fe in LaFeO3 gb [46]; (26) Fe in LaFeO3 b [46]; (27) 141 Pr in LaCoO3 b [40]; (28) 141 Pr in LaFeO...…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abbreviations: ppolycrystalline; sc-single crystal; c-cubic; b-bulk; gb-grain boundaries. (1) Ho in p BaTiO3 gb [11]; (2) Ho in p BaTiO3 b [11]; (3) Ni in p Ba(Ho,Ti)O3 [10]; (4) Ni in sc BaTiO3 [10]; (5) Ni in p BaTiO3 [10]; (6) Si in MgSiO3 [39]; (7) 49 Ti in sc (La,Sr)TiO3 [25]; (8) Zr in sc BaTiO3 [12]; (9) 141 Pr in LaFeO3 gb [40; (10) 141 Pr in LaCoO3 gb [40]; (11) Co in LaCoO3 gb [41]; (12) Cr in LaMnO3 [42];(13) Mn in LaCoO3 [43]; (14) Co in LaCoO3 b [41]; (15) 141 Pr in LaMnO3 [40]; (16) Co in GdCoO3 [44]; (17) Co in EuCoO3 [44]; (18) Co in SmCoO3 [44]; (19) Co in NdCoO3 [44]; (20) Co in PrCoO3 [44]; (21) 50 Cr in (La,Ca)CrO3 gb [45]; (22) Co in LaCoO3 [44]; (23) Mn in LaMnO3 b [42]; (24) Mn in LaMnO3 gb [42]; (25) Fe in LaFeO3 gb [46]; (26) Fe in LaFeO3 b [46]; (27) 141 Pr in LaCoO3 b [40]; (28) 141 Pr in LaFeO...…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been shown that A-site diffusion is faster than B-site diffusion in BZ [17]. Knowledge of the difference in the cation mobility at the different cation sub-lattices is vital for the understanding of the long-term stability of the materials in chemical potential gradients [19]. Moreover, cation diffusion is also relevant for the reactivity of materials with e.g., CO 2 , as recently shown for BZ-materials [20].…”
Section: Introductionmentioning
confidence: 99%
“…It can be anticipated that various ageing phenomena may be explained by such kinetics. [ 2,[46][47][48] Thus, a quantitatively precise description of the kinetics of chemical composition change, not only in simplifi ed limiting cases but in particular in the complex intermediate situations, as treated in the present publication is of outmost importance.…”
Section: Relevance For Functional Materialsmentioning
confidence: 99%
“…Even if one ionic component is overwhelmingly responsible for the ionic conductivity, this fi nite mobility of a further component leads to serious, typically unwanted long-time effects. [ 2 ] There are various situations where two ionic species can be similarly conductive, e.g., in proton conducting oxides. Though there the peculiarities appear in a most striking form and can be easily experimentally measured, the treatment to be outlined is general.…”
Section: Introductionmentioning
confidence: 99%
“…The present changes appear to result from a combination of the above-noted materials de-stabilization effects with gradients in oxygen chemical potential and electrical potential that are present during cell operation. It is known that morphological instabilities, kinetic decomposition, and kinetic demixing can occur in oxide materials under such gradients [18]. Gradients in the oxygen chemical potential, l O , are present at the anode/electrolyte interface since the elec- …”
Section: Discussionmentioning
confidence: 99%